Electro-Kinetic Studies on Comparative Properties of a Liquid Membrane and an Animal Membrane - Shukla, P.C.; Shukla, Alok (Asian Journal of Chemistry, 2010)
Two sets of membrane i.e., liquid membrane generated by cholesterol and urinary bladder of goat as animal membrane have been chosen for experimental studies. Maximum conversion efficiency, figure of merit and degree of coupling have been computed for number of permeants. Alternative explanations of micturition phenomena in terms of frictional co-efficient have been given and results have been analyzed in terms of non-equilibrium thermodynamics.